Three-dimensional Stratigraphy Reconstruction and GIS – Postprocessing Issues in Archaeological field 3D Documentation - Wojciech Ostrowski (Ksiegarnia Akademicka Publishing, 2019)
This paper aims to present the results of experiments which allowed us to propose up-to-date method of 3D visual representation of explored archaeological layers. Considering the destructive nature of excavations, the correct documentation of an exploration, which offers an insight both into the decision-making process taking place on site, and into the most faithful representation of the examined material, presents a fundamental challenge for a field archaeologist. The aim of the experiments presented here was to test three methods of creating 3D models of successive archaeological layers (contexts) recorded during an exploration. The presented findings show that the method of editing point clouds using open-source software prior to importing the model of the reconstruction of the explored layer into GIS software, is the best solution from the point of view of both the effort and time required, and it can definitely be suggested as the standard procedure of creating the graphical bases for an archaeological database.